Seasonal dependence of cadmium molecular effects on Mytilus galloprovincialis (Lamarck, 1819) protamine‐like protein properties. Issue 10 (17th July 2019) - Piscopo, Marina
Abstract: Mussels have a seasonal reproduction and cadmium is a common stressor in estuarine and coastal environments. In previous studies, we have shown that exposure to subtoxic doses of cadmium produced alterations in the properties of winter Mytilus galloprovincialis sperm protamine‐like (PL) proteins. In this study, it was analyzed the possibility that these cadmium effects may be seasonal. Winter and summer mussels were exposed to CdCl2, and it was tested the PL‐proteins for cadmium bioaccumulation, electrophoretic pattern, DNA binding, and potentiality to induce DNA oxidative damage. It was found that cadmium exposure did not produce the same effects on PL‐proteins of summer mussels that were produced on PL‐proteins of winter mussels, that is: cadmium bioaccumulation, alterations in the acetic acid‐urea polyacrylamide gels (AU‐PAGE) and sodium dodecyl sulfate‐PAGE pattern, a reduced DNA binding affinity and the ability to induce DNA oxidative damage. PL‐proteins from summer mussels, apart from not being affected by all the abovementioned effects of cadmium, also showed a very low DNA binding affinity, independent of cadmium exposure. This study reveals clock‐associated seasonal responses to cadmium in M. galloprovincialis . Understanding the mechanisms through which environmental signals guide biological rhythms is fundamental to understanding the seasonal sensitivity of this bioindicator, to use M. galloprovincialis in appropriate seasonal periods. Abstract : The molecular effects of cadmium on Mytilus galloprovincialis protamine‐like proteins (PL‐proteins) depend on seasonality PL‐proteins from winter and not from summer mussels exposed to CdCl2 accumulate cadmium, undergo structural changes; undergo reduced DNA binding affinity; induce DNA oxidative damage This study reveals clock‐associated seasonal responses to cadmium in M. galloprovincialis .